Experiential and Textual Functions Analysis of Minangkabau Song Lyric “Taragak Pulang” - Uswar, Yenita; Harahap, Dina Irmayanti (Association of Language Teachers in Southeast Asia (ALTSA), 2024)
This research investigates the results of SFL (Systemic Functional Linguistics) study on the Experiential and Textual functions in the Minangkabau Song Lyric “Taragak Pulang”. The primary goal of this research is to describe many sorts of Processes, Participants and Circumstances featured in experiential function in that song, and also to analyze the Theme and Rheme in Textual Function. The research design of this analysis is a descriptive qualitative method. This research aims to analyze the experiential function and textual Function of sentences as an exchange in the Minangkabau Song Lyric